PO055 Results of an rct of self-management education in epilepsy: smile-uk. (1st December 2017) - Ridsdale, Leone; Wojewodka, Gabriella; Robinson, Emily; Landau, Sabine; Noble, Adam; Taylor, Stephanie; Baker, Gus; Richardson, Mark; Goldstein, Laura
Abstract : Introduction: People with epilepsy (PWE) want to learn about self-management. No course tested in UK. Methods: Mixed-methods RCT evaluating group 2 day self-management education for poorly controlled epilepsy. Participants' characteristics described at baseline, a sub-sample purposefully interviewed at 6 months, outcomes analysed at 1 year. Outcomes: primary, quality of life (QOLIE-31-P); secondary: seizure frequency, psychological distress, self-mastery and felt-stigma. Results: Enrolled 404 participants with median 18 years since diagnosis, 69%≥10 seizures in the prior year, 46% reported co-morbidity, 64% current anxiety, 28% borderline or case-level depression, and 63% felt stigmatised. Participants' mean QOLIE-31-P was 66 out of 100 (range 25–99). In decreasing order, associated with low QOLIE-31-P: depression, low self-mastery, anxiety, feeling stigmatised, history of medical/psychiatric comorbidity, low self-reported medication adherence, and greater seizure frequency. Process evaluation interviews found that PWE felt socially isolated. They gained confidence from interactive groups. Results at 1 year outcome will be presented. Conclusions: PWE and persistent seizures experience low QoL, with psychological and social characteristics more closely associated than clinical characteristics. Group learning helps PWE overcome isolation and gain confidence. The views and opinions expressed therein are those of the authors and do not necessarily reflect those of the HTA, NIHR, NHS or the Department of Health.